La rappresentazione della giustizia penale attraverso le cronache giudiziarie di fine ottocento - De Salvo, Patrizia (Acta Histriae, 2007)
In the late 19th century judicial events would enter the circuits of public consciousness that was formed around and involved by court stories and through trial narratives published by the press. The objectives of the research of these media (magazines, newspapers, leaflets, monographs) included the verification of the public perception of new and different institutions of procedural law, such as the jury, oral discussion, etc., that had evoked numerous criticisms including among the most prominent representatives of the Italian penal doctrine
Keywords: 19.st.; criminal law; javno mnenje; kazensko pravo; kronike; porota; sodstvo